Stress concentration in open hole Laminate composites under bending: Potential application in dental implant prosthesis - Alves, Harlei Augusto Bueno [UNESP]; Monticeli, Francisco MacIel [UNESP]; Lobo, Carolina MacHado Martinelli [UNESP]; Shiino, Marcos Yutaka [UNESP] (FapUNIFESP (SciELO), 2022)
Carbon fiber reinforced polymer (CFRP) have been gaining prominence in replacing metallic alloys for infrastructure in prostheses, with the possibility of edentulous patients to acquire fixed prostheses. For this, procedures are required to connect these implants to the implant-supported fixed prosthesis, such as holes and notches that can reduce their mechanical properties. In addition, the infrastructure requires longer cantilevers, causing greater stress on the prosthetic system. Then, the objective is to analyze the stress concentration in the CFRP subjected to bending loads with holes (4 and 6 mm diameter to verify the influence of the diameter-to-width ratio) in four-point-bending test. Two composite laminates were evaluated: one with thermoplastic matrix of poly(phenylene sulphide) PPS; and another with epoxy matrix combined with carbon fibers fabric. The presence of holes in the studied dimensions did not present significant differences in the flexural modulus and maximum bending strength. Therefore, the use of CFRP showed some advantage regarding the reduced effect of stress concentration compared to metallic alloys.
Keywords: Bending moment; Buckling; Dental prosthesis; Fracture; Residual strength